Pengelolaan Arsip Statis di Dinas Kearsipan dan Perpustakaan Kabupaten Padang Pariaman - Utari Ramadhani; Desriyeni Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractThe writing of this paper discusses the management of statistical records in the Padang Pariaman District Archives and Library. The purpose of this paper is to find out how to manage statistical records in the Padang Pariaman District Archives and Library; explain the installation procedure and how to use electronic files; describe investments found in managing statistical records; illustrates the efforts made to overcome difficulties in managing statistical records. This research was conducted using descriptive methods with accurate factual facts about the facts, facts and facts investigated. Data collected through observation, interviews, and literature studies. Based on the research that has been done, it can be concluded first, the management of statistical records in the Padang Pariaman District Archives and Library Services includes: (a) acquisition files, (b) processing statistical records; (c) preservation of statistical files; and (d) Access. Second, the procedure for installing and using electronic records at the Padang Pariaman District Archive and Library Service includes: (a) Xampp installation as a MySQL database server; (b) storage application as an electronic file storage device. Third, regulating what is in the administrative archive at the Padang Pariaman District Archives and Library Office includes: (a) implementation of the agreement not all archive creators who submit statistical records to the Padang Pariaman District Archives and Library Office; (b) Implementation of implementations that require a long time (c) Implementation of preservation as needed; (d) while access activities still use conventional methods. Fourth, efforts were made to overcome the challenges in managing statistical archives: (a) by dragging archives makers who sent statistical archives to the Padang Pariaman District Archive and Library Services; (b) carrying out regular organizing processing from the creator of the archive, labeling the boxes, adding shelves to manage the volume of archives; (c) Implementation of maintenance by providing adequate equipment (d) when supporting access also uses digital technology and provides supporting facilities and infrastructure.Keywords: management, archives, statis